THE QUANTIFYING OF BIOMASSA AT OIL PALM PLANTATION IN LANGKAT, NORTH SUMATERA - Muhdi (Jurnal Online Pertanian Tropik, 2015)
Quantifying oil palm plantation contribution to global carbon budgets is needed. Biomass variation of oil palm plantation practices through allometric models that can be used to asses oil palm plantation. The objectives of this research were to find the biomass variation of oil palm plantation in Langkat, North Sumatera. The research was done in two steps. Firstly, data collecting was at oil palm plantation. The second step was analyzed biomass in a laboratory. Measurement of parameters is done by 9 (nine) permanent sample plots (PCP) with line block method in 5 years, 10 years and 15 years. The size of the plots was 20 m x 20 m (400 m2) that distance to another plot was 10 m x 10 m (100 m2) used random sampling. This research found that the models of biomass in oil palm plantation was W = 0.00597D1.000Hbp 1.142.